Disentangling the complex roles of markets on coral reefs in northwest Madagascar - Eva Maire (Resilience Alliance, 2020)
Rapid degradation of the world's coral reefs jeopardizes their ecological functioning and ultimately imperils the well-being of the millions of people with reef-dependent livelihoods. Ecosystem accessibility is the main driver of their conditions, with the most accessible ecosystems being most at risk of resource depletion. People's socioeconomic conditions can change as they get further from urban centers and can profoundly influence people's relationship with the environment. However, the mechanisms through which increasing accessibility from human societies affects natural resources are still unclear. A plausible mechanism through which markets influence the environment is through the socioeconomic changes that tend to accompany accessibility. We used social and ecological data from 10 coastal communities and 31 reefs in northwest Madagascar to (i) unravel the respective influences of the local fish market and coastal communities on reef fish biomass and (ii) investigate how communities' socioeconomic and resource use characteristics change with increasing proximity to markets. We used generalized additive models to reveal that reef fish biomass is strongly related to the accessibility of both markets and local communities. We also highlight that the ways coastal communities use marine resources changes predictably with market proximity. More precisely, market proximity affects fishing gear (technique effect), wealth, and selling strategies (scale effect) of coastal communities. Our findings emphasize the need to better quantify links between markets and fishing communities through household-level surveys to implement market-based actions that could help to regulate the effect of markets on both fish stocks and fishing communities.